Investigating the Mechanisms behind the Positive Food Effect of Abiraterone Acetate: In Vitro and Rat In Situ Studies - Marlies Braeckmans; Patrick Augustijns; Raf Mols; Cécile Servais; Joachim Brouwers (MDPI AG, 2022)
The anticancer agent abiraterone suffers from an extensive positive food effect after oral intake of the prodrug abiraterone acetate (Zytiga). The underlying processes determining postprandial abiraterone absorption were investigated in this study. The impact of lipids and lipid digestion products on (i) the solubility of abiraterone acetate and abiraterone, (ii) the conversion of abiraterone acetate to abiraterone, and (iii) the passive permeation of abiraterone was determined in vitro. The interaction of abiraterone acetate and abiraterone with vesicles and colloidal structures in the simulated fed state media containing undigested lipids and lipid digestion products enhanced the solubility of both compounds but limited the esterase-mediated hydrolysis of abiraterone acetate and the potential of abiraterone to permeate. Rat in situ intestinal perfusion experiments with a suspension of abiraterone acetate in static fed state simulated media identified abiraterone concentrations in the perfusate as the main driving force for absorption. However, experiments with ongoing lipolysis in the perfusate highlighted the importance of including lipid digestion as a dynamic process when studying postprandial abiraterone absorption. Future research may employ the in situ perfusion model to study postprandial drug absorption from a dynamic lipolysis-mediated intestinal environment to provide reference data for the optimisation of relevant in vitro models to evaluate food effects.